Characterizing waterlogging tolerance using multiple selection indices in bread wheat (Triticum aestivum) - SINGH, GYANENDRA; KUMAR, PRADEEP; GUPTA, VIKAS; TYAGI, B S; SINGH, CHARAN; SHARMA, A K; SINGH, G P (The Indian Journal of Agricultural Sciences, 2020)
WL stress significantly affected grain yield, biological yield, tillers per meter, plant height and spike weight. The plant height, tillers per meter, spike weight, and biological yield were found to be positively and significantly correlated with grain yield under WL conditions. Among these traits, biological yield has maximum contribution towards WL tolerance and can be used for selection of tolerant genotypes. Significant and desirable correlation of different selection indices, viz. HM, MP, YSI, STI and PRGY indicated that any one of these can be used interchangeably to select stress tolerant genotypes.